Migraine, Stroke, and Cervical Arterial Dissection: Shared Genetics for a Triad of Brain Disorders With Vascular Involvement. (1st February 2022) - Daghals, Iyas; Sargurupremraj, Muralidharan; Danning, Rebecca; Gormley, Padhraig; Malik, Rainer; Amouyel, Philippe; Metso, Tiina; Pezzini, Alessandro; Kurth, Tobias; Debette, Stéphanie; Chasman, Daniel
Abstract : Background and Objectives: Migraine, stroke, and cervical artery dissection (CeAD) represent a triad of cerebrovascular disorders with pairwise comorbid relationships and vascular involvement. Larger samples and recent advances in methodology invite systematic exploration of their shared genetics. Methods: Genetic analyses leveraged summary statistics from genome-wide association studies of the largest available samples of each disorder, including subtypes of stroke (ischemic stroke, large artery stroke, small vessel stroke, and cardioembolic stroke) and migraine (with aura and without aura). For each pair of disorders, genetic correlation was assessed both on a genome-wide basis and within independent segments across the genome including known specific loci for each disorder. A cross-trait meta-analysis was used to identify novel candidate loci. Finally, potential causality of migraine susceptibility on stroke and CeAD was assessed by Mendelian randomization. Results: Among all pairs of disorders, genome-wide genetic correlation was observed only between CeAD and migraine, particularly MO. Local genetic correlations were more extensive between migraine and CeAD than those between migraine and stroke or CeAD and stroke and revealed evidence for novel CeAD associations at rs6693567 ( ADAMTSL4/ECM1 ), rs11187838 ( PLCE1 ), and rs7940646 ( MRVI1 ) while strengthening prior subthreshold evidence at rs9486725 ( FHL5 ) and rs650724 ( LRP1 ). At known migraine loci, novel associations with stroke had concordant risk alleles for small vessel stroke at rs191602009 ( CARF ) and for cardioembolic stroke at rs55884259 ( NKX2-5 ). Known migraine loci also revealed novel associations but with opposite risk alleles for all stroke, ischemic stroke, and small vessel stroke at rs55928386 ( HTRA1 ), for large artery stroke at rs11172113 ( LRP1 ), and for all stroke and ischemic stroke at rs1535791 and rs4942561 (both LRCH1 ), respectively. rs182923402 (near PTCH1 ) was a novel concordant locus for migraine and cardioembolic stroke. Mendelian randomization supported potential causal influences of migraine on CeAD (odds ratio [95% confidence interval] per doubling migraine prevalence = 1.69 [1.24–2.3], p = 0.0009) with concordant risk, but with opposite risk on large artery stroke (0.86 [0.76–0.96], p = 0.0067). Discussion: The findings emphasize shared genetic risk between migraine and CeAD while identifying loci with likely vascular function in migraine and shared but opposite genetic risk between migraine and stroke subtypes, and a central role of LRP1 in all 3 cerebrovascular disorders.